Breathable and Wearable MXene-Decorated Air-Laid Paper With Superior Folding Endurance and Electromagnetic Interference-Shielding Performances - Ma, Chang; Liu, Tong; Xin, Wei; Xi, Guo-Qiang; Ma, Ming-Guo (Frontiers in Materials, 2019)
With the development of electronic information technology, electromagnetic pollution has become thorny environmental problem. 2D transition metal carbides/nitrides (MXenes) are regard as the next-generation material for electromagnetic interference (EMI) shielding due to their excellent electrical conductivity and large specific surface area. Flexible membrane-like MXene-based materials in EMI shielding have received tremendous attention, but very few of them can meet the actural needs of durability, stable, and breathability in daily life. In this article, we chose air-laid paper as flexible substrate for preparing MXene-decorated composite paper by a simple “dipping and drying” method. This composite paper exhibits a high electrical conductivity of 173.0 S m-1, a superior EMI shielding efficiency (more than 90% of the electromagnetic waves in X-band), a good mechanical flexibility (more than 9.8 × 104 times) and breathability. Moreover, the composite paper shows excellent durability after folding or soaking in artifical sweat. Therefore, the as-prepared MXene-decorated composite paper has promising application in EMI shielding clothing fields.